Anisotropic fracture and energy characteristics of a Tibet marble exposed to multi-level constant-amplitude (MLCA) cyclic loads: A lab-scale testing. (1st March 2021) - Wang, Y.; Yi, Y.F.; Li, C.H.; Han, J.Q.
Highlights: Fatigue volumetric deformation of marble is impacted obviously by interbed structure. Rock damage displays a first fast grow then steady propagation trend within a cyclic stage. A new damage evolution model was proposed based on rock axial strain to describe damage evolution. Failure mode of anisotropic marble is structural dependent and it changes from tensile splitting to mixed shear-tension. Abstract: Rock mass is often subjected to complicated stress disturbance in many civil and mining engineering. This work aims to investigate the fatigue mechanical characteristics of marble having different interbed orientation subjected to multi-level constant-amplitude (MLCA) cyclic loads. The impacts of interbed structure on rock fracture and energy characteristics were investigated and characterized experimentally. The experimental results reveal that the deformation, strength, lifetime, damping characteristics, and energy release and dissipation are all impacted by the interbed structure. From the change of hysteresis loop shape, damping ratio, and dissipated energy, a two-phase damage evolution characteristic at each cyclic loading stage is observed. The hysteresis loop area, damping ratio and dissipated energy all decrease with increasing cyclic number within a cyclic loading stage. At the start of each cyclic stage, the sudden growth of axial stress contributes a lot to the rock damage compared to the followed cyclic loads. In addition, based on the energy dissipation principle, a fatigue damage model was proposed to describe rock accumulative damage. It is shown that the model can well describe the damage accumulation regardless the rock structure. Moreover, good agreement is found between the CT images and energy analysis, and it is suggested that it is the rock structure that controls the energy dissipation and release pattern.